Diet selection in goats: a test of intake-rate maximization - Illius, A. W.; Gordon, I. J.; Elston, D. A.; Milne, J. D. (Ecology (Durham), 1999)
The mechanisms of diet choice by herbivores are poorly understood. We tested whether the preference of goats among five grass species was accounted for by differences in intake rate or differences in species-specific attributes of the grasses. When offered a choice between grass species, the goats selected diets that tended to maximize intake rate. Only a small amount of the residual variation was explained by the individual preference of goats for each grass species. The animals exhibited partial preferences, only leaving the lower intake-rate alternative ungrazed in a quarter of the trials. It is argued that the most likely explanation of this is the difficulty of discriminating between alternatives of similar intake rate. Discrimination error is likely to be a general explanation of mixed diets in herbivores, regardless of whether other explanations, such as rate maximization subject to nutrient constraints, also apply.